2008
DOI: 10.1021/es703062f
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Mass Flows of Fluorochemicals in the Glatt Valley Watershed, Switzerland

Abstract: Fluorochemicals are persistent contaminants that are globally distributed in air, water, sediments, and biota. Wastewater treatment plants (WWTPs) play an important role in mitigating pollutant releases from municipalities to aquatic and terrestrial environments. However, because WWTPs are point sources of fluorochemicals, it is important to understand their contribution to fluorochemical burdens in the greater context of watersheds. To this end, over a 1 week period, the mass flows of 11 fluorochemicals from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
94
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(103 citation statements)
references
References 33 publications
(65 reference statements)
6
94
1
1
Order By: Relevance
“…So far, several previous studies have reported the occurrence of PFASs, especially PFOA and PFOS in WWTPs and tap water globally (Ericson et al, 2008;Huset et al, 2008;Jin et al, 2009;Quiñones and Snyder, 2009;Quinete et al, 2009;Arvaniti et al, 2012;Zhang et al, 2013;Schwanz et al, 2016). However, very limited information is available for the various PFASs in DWTPs (Shivakoti et al, 2010;Takagi et al, 2011;Thompson et al, 2011;Eschauzier et al, 2012;Flores et al, 2013).…”
Section: Concentrations and Composition Profiles Of Pfass In Dwtpsmentioning
confidence: 99%
“…So far, several previous studies have reported the occurrence of PFASs, especially PFOA and PFOS in WWTPs and tap water globally (Ericson et al, 2008;Huset et al, 2008;Jin et al, 2009;Quiñones and Snyder, 2009;Quinete et al, 2009;Arvaniti et al, 2012;Zhang et al, 2013;Schwanz et al, 2016). However, very limited information is available for the various PFASs in DWTPs (Shivakoti et al, 2010;Takagi et al, 2011;Thompson et al, 2011;Eschauzier et al, 2012;Flores et al, 2013).…”
Section: Concentrations and Composition Profiles Of Pfass In Dwtpsmentioning
confidence: 99%
“…Several studies have predicted the expected concentrations of pharmaceuticals in surface waters using estimates of mass loading, dilution and in-stream attenuation, here understood as the reduction of the concentration of pharmaceuticals along the river segment by processes different than dilution (Huset et al 2008;Alder et al 2010). Reliability of these models is however constrained by the high variability in chemical emissions from WWTPs and attenuation in surface waters (Pistocchi et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…PFAs have also been studied in municipal wastewater treatment plants (WWTPs) [7,33,37,42,43,[48][49][50]64,69,80,[136][137][138][139][140][141] where sorption of contaminants to organic matter and settling with particulates in grit chambers, trickling filters, rotating biological contactors, and primary/secondary clarifiers, as well as sorption to activation carbon if this polishing step is present, is a major removal process from the final effluent stream. Although it has been previously noted that a means of estimating K oc values for the C 1 through C 8 PFAs would be valuable in better understanding PFA profiles within WWTPs, [137] the potential range of PFA precursors that are subject to biological and physicochemical degradation into PFAs (e.g., perfluoroalkyl sulfonamides, fluorotelomers, etc.)…”
mentioning
confidence: 99%
“…Caution must also be exercised in neglecting sorption losses to sediments in riverine PFA mass balance studies, particularly where only PFAs are monitored in upstream and downstream waters and wastewater inputs and a mass balance is achieved, as has been previously done. [37] In these studies, PFA precursors could be degrading in situ within a particular stream reach as an additional (and unaccounted for) PFA input with fluxes that offset PFA losses to sediments.…”
mentioning
confidence: 99%